The Restoration of Latin America's Access to Voluntary Capital Market Financing : Developments and Prospects - El-Erian, Mohamed (IMF Working Papers; Working Paper ;, 1991)
After a prolonged and almost total reliance on debt restructurings and concerted new money facilities, several Latin American countries have, over the last two years, mobilized voluntary financing from international capital markets. Although the phenomenon is still relatively limited in terms of volume and number of borrowers, it has nevertheless attracted considerable attention. The paper reviews the nature, magnitude and terms of the market re-entry process and, by drawing upon recent country experiences, analyzes the factors that have facilitated it. This provides the basis for a discussion of the key elements affecting the short-term prospects for Latin American private and public sector voluntary debt and equity financing from international capital markets.